The Influence of Nordic Walking on Physical Fitness of Elderly People - Vaida Šokelienė; Vida Janina Česnaitienė (Baltic Journal of Sport and Health Sciences, 2018)
Research background and hypothesis. Nordic Walking is a form of physical activity which is rapidly gaining its popularity and is suitable for people of various ages and health conditions. We hypothesized that after 12 weeks of Nordic Walking exercises elderly people would experience certain changes, including increased flexibility of the lumbar spine area, increased strength endurance of the lower limbs, better aerobic endurance, decreased proportional fat mass. Research aim was to determine and asses the influence of Nordic Walking on the physical capability of elderly people. Research methods. The study included 41 subjects (11 men and 30 women): their average age was 65 ± 5 years. Physical activity of the subjects was evaluated according to their physical activity level and intensity evaluation questionnaire (RAPA). In order to determine physical fitness of the subjects we performed calf endurance test based on P. Mark and S. Tremblay’s (1992) proposed methodology, lumbar spine flexibility was evaluated by the “sit- reach” test, spirometry, aerobic endurance test. The subjects performed Nordic Walking training sessions two times a week. The duration of the study was 12 weeks. Research results. The people who engaged in the Nordic Walking practice sessions showed improved indicators of aerobic endurance, smaller body mass and lower ratio of waist/hip sizes. The flexibility of the lumbar spine area increased for the people who had been physical inactive. Discussion  and  conclusions.  Nordic Walking  holds  a  positive  impact  on  the  physical  capability  of  elderly people. Engagement in the Nordic Walking exercises has a more obvious effect on the physical capability of the people who are less physically active than of the people who are more physically active.